Lazarus phenomenon in trauma. (February 2020) - Mahon, Timothy; Kalakoti, Piyush; Conrad, Steven A.; Samra, Navdeep S.; Edens, Mary Ann
Abstract: Lazarus phenomenon embodies auto-resuscitation, aka the return of spontaneous circulation following termination of cardiopulmonary resuscitation. Limited or no literature exists that describes auto-resuscitation in trauma. In the current report, we describe a case of an older woman that presented with poly-traumatic injuries following a motor vehicle collision. The aggressive resuscitation efforts failed, and the patient witnessed a pulseless electrical activity; however, nine-minutes after cessation of resuscitation efforts, the patient experienced auto-resuscitation. In addition to the sequel of events following the presentation, the report highlights the management dilemma and ethical implications relating to the observation period for auto-resuscitation in cases of donation after circulatory death, where the urgency to harvest the organs to ensure maximum viability is in direct opposition to ensuring enough time has elapsed to rule out auto-resuscitation. Guidelines on an appropriate period for observation in auto-resuscitation patients queued for organ donation are warranted, keeping in lieu viability of organs following death.